Voice of fear [large type] - Graham, Heather (Graham, Heather. Krewe of hunters, 2022)
"FBI agent Jordan Wallace is close to cracking the human trafficking case she's been working, when she does the one thing she should never do: let her guard down. The botched undercover mission is semisalvaged by the last-minute appearance of criminal psychologist Patrick Law, but Jordan can't imagine making a worse first impression. Especially when she's partnered with Patrick moving forward. Patrick's innate ability to get inside a criminal's head is an asset for the Krewe of Hunters. But Jordan wishes she could protect her own thoughts from her new partner. Patrick assures her that both she and her thoughts are safe with him, but Jordan's less sure about her heart. Letting someone have her back has never been her strong suit, but with a dangerous killer still at large, trusting in Patrick might be the only thing keeping them alive"-- Provided by publisher.